(untitled) (Quaestiones Disputatae: temas en debate, 2017)
The purpose of this article is to share the results of an investigation into students’ identity as future psychologists through academic literary practices in English. The study provided students an appropriated environment, based on topics about psychology, which was characterized by the students free production. They had the opportunity to make their own choices, as well as discuss, analyze, give opinions or diagnosis about the topics studied (annex 8). Data was collected through students’ journals, written samples and semi-structured interviews. The findings showed the students’ identity with their own field of study along the following aspects: the literacy practices enabled them to read and write about topics of daily life from a critical view point, they were building their identity through their interest for analysing and arguing problematic situations; additionally, the use of specialized vocabulary, along with the linking of theory and practice are evidenced in this study.